Intra-articular displacement of an avulsed medial (internal) epicondyle ossification centre in the paediatric elbow: a radiographic finding not to be missed. Issue 11 (10th November 2019) - Qadeer, Amir; Paddock, Michael
Abstract : We present the case of an 11-year-old girl who was presented to the Emergency Department with right elbow pain and swelling following a fall. Radiography demonstrated intra-articular displacement of an avulsed medial epicondyle ossification centre, which was not readily identified at presentation. She proceeded to an uncomplicated open reduction and internal fixation.